Design of distribution system of centralized industrial area in Halul Island, Qatar - Tambis, Ariel T. (Manila Professional Regulation Commission, 2015)
The project is developing a centralized industrial area, easily accessible by land (on the island) and sea, with all the required facilities to confine fabrication, maintenance, repair, blasting, painting and the like by Marine Department (MR), QP Maintenance Departments and contractors, so that the rest of the island is free from environmental pollution and safety hazards arising from such activities. Part of this area will be used for containing the relocated marine stores and workshops. In addition, it is proposed to centralize contractor's project site offices and stores location of temporary camp. The centralized industrial area is divided into area A and area B. Area A will be used by QP and Area B to be used by contractors. Blasting I painting booths common for both QP and the contractor's area to be provided at the southern side of Area A to reduce pollution. The contractor's access to this common area will be from outside of Area A and office complex at Area B will be shared between contractors and Total E&P Qatar (TEPQ). For carrying out the Scope of Work (SOW), MIS Qatar Design Consortium Company (QDC) carried out the Front End Engineering Design (FEED) and the Detailed Engineering Design was awarded to Orientals Enterprises LLC with COWl as the design consultant. However, after approval of detailed engineering deSign, QP has requested a work change request from the original SOW. This additional scope is to replace the three diesel driven air compressors by electrical compressors which will be the main focus of this Technical Engineering Report.
Technical report submitted in partial fulfillment of the requirements for the licensure examinations for professional electrical engineers.
E2-659G donated by Mr. Jaime E. Mendoza.
Keywords: Electric power distribution